1999
DOI: 10.1136/jcp.52.9.658
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of IL-10 and IL-12 (p40) mRNA in Helicobacter pylori infected gastric mucosa: relation to bacterial cag status and peptic ulceration.

Abstract: Aims-To investigate interleukin (IL)-12(p40) and IL-10 mRNA expression levels in the gastric mucosa in relation to H pylori cag status, peptic ulceration, and histopathology. Methods-In 81 dyspeptic patients, antral and corpus biopsies were taken for reverse transcriptase polymerase chain reaction (RT-PCR) and histology. G3PDH (control) and IL-10 and IL-12 were coamplified in a duplex PCR and the ratios of cytokines to G3PDH were determined. Bacterial ureA and cagA status was determined by RT-PCR. (J Clin Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
3
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 51 publications
8
53
3
2
Order By: Relevance
“…These results are consistent with previous findings, indicating that H. pylori infection is related to a high expression of IL-10 in the gastric mucosa both on mRNA and protein level (Bodger et al, 2001;Hida et al, 1999). IL-10 has long been considered a potent anti-inflammatory cytokine strongly implicated in H. pylori infection (Bodger et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…These results are consistent with previous findings, indicating that H. pylori infection is related to a high expression of IL-10 in the gastric mucosa both on mRNA and protein level (Bodger et al, 2001;Hida et al, 1999). IL-10 has long been considered a potent anti-inflammatory cytokine strongly implicated in H. pylori infection (Bodger et al, 2001).…”
Section: Discussionsupporting
confidence: 83%
“…Studies have shown that the H. pylori-induced inflammatory response is associated with Th1-mediated cellular responses [28,40], with higher expression of interferon-c (IFN-c) [40], IL-10, and IL-12 [41]. Particularly strong effects were seen in those possessing the pathogenic CagA + strains [28,41].…”
Section: Discussionmentioning
confidence: 98%
“…Total RNA was extracted from endoscopic gastric biopsies using Catrimox-14 (VH Bio Ltd.) and was treated with DNase I (Gibco Life Technologies). Purified RNA was reverse transcribed in 20 l of solution using 0.5 g of Random Primers (Promega) as previously described (28,62). Expression of genes of interest was examined by semiquantitative RT-PCR using primer sequences described in Table 1.…”
Section: Confirmation Of Differential Expression Of Genes In Vitro Anmentioning
confidence: 99%